Ultrahigh-performance supercritical fluid chromatography / mass spectrometry in the lipidomic analysis - Wolrab, Denise; Peterka, Ondřej; Chocholoušková, Michaela; Holčapek, Michal (Elsevier Science BV, 2022)
Ultrahigh-performance supercritical fluid chromatography/mass spectrometry (UHPSFC/MS) is one of the fastest analytical approaches for high-throughput lipidomic analysis covering a wide range of lipid categories and classes. Lipid class separation and lipid species separation are two main separation modes available for the UHPSFC analysis of lipids. The mechanism of the lipid class separation mode is com-parable to that of hydrophilic interaction liquid chromatography (HILIC). The direct comparison of HILIC -ultrahigh-performance liquid chromatography (HILIC-UHPLC) and UHPSFC shows the applicability of UHPSFC/MS for high-throughput quantitation of both nonpolar and polar lipid classes, the faster analysis time, and comparable reproducibility and sensitivity. The retention mechanism of the lipid species separation mode is comparable to reversed-phase UHPLC, but the nonpolar character of supercritical carbon dioxide (scCO(2)) provides a different selectivity compared to that of conventional RP-UHPLC. The introduction of various hyphenation interfaces to MS broadens the applicability and sensitivity range of UHPSFC/MS using scCO(2) as the main component of the mobile phase. The addition of ionic additives (volatile salts, acids, and bases) to the modifier improves the separation of medium to polar lipids. Furthermore, UHPSFC/MS has also a great potential in the chiral separation of lipids, but the field has not yet been fully explored.
Ultravysoko-účinná superkritická fluidní chromatografie / hmotnostní spektrometrie v lipidomické analýze
Keywords: ultrahigh-performance supercritical fluid; chromatography; ultrahigh-performance liquid; lipids; lipidomics; mass spectrometry; high-throughput lipidomics; polar and nonpolar lipids; ultravysoko-účinná superkritická tekutina; chromatografie; ultravysoko-účinná kapalina; lipidy; lipidomika; hmotnostní spektrometrie; polární a nepolární lipidy